1974
DOI: 10.1071/bi9740047
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Testicular Function. I. Quantitative Effects of FSH, LH, Testosterone and Dihydro-testosterone on Restoration and Maintenance of Spermatogenesis in the Hypophysectomized Rat

Abstract: Male Wistar rats were hypophysectomized and the effects on spermatogenesis were quantified by stereological techniques. Restoration of normal spermatogenesis was attempted 32 days after hypo-physectomy by treatment with FSH (designated F), LH (L) or testosterone (T) singly or in combina-tion for a further 32 days. In another experiment, maintenance of spermatogenesis was attempted using FSH (F), testosterone (T) or dihydrotestoterone (D). Treatment began two days after hypo-physectomy and was continued for a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
(39 reference statements)
0
10
1
Order By: Relevance
“…Subsequent administration of T to GnRH-immunized rats has been shown to quantitatively restore complete spermatogenesis and fertility [6,22] over an 8-wk period, indicating that FSH is clearly not an absolute requirement for restoration of spermatogenesis despite widespread speculation to the contrary. This result, combined with the observed inability of T to restore spermatogenesis quantitatively in hypophysectomized rats [33][34][35][36], suggests that pituitary hormones other than, or in addition to, FSH may play a major role in the restoration of spermatogenesis.…”
Section: Discussionmentioning
confidence: 61%
“…Subsequent administration of T to GnRH-immunized rats has been shown to quantitatively restore complete spermatogenesis and fertility [6,22] over an 8-wk period, indicating that FSH is clearly not an absolute requirement for restoration of spermatogenesis despite widespread speculation to the contrary. This result, combined with the observed inability of T to restore spermatogenesis quantitatively in hypophysectomized rats [33][34][35][36], suggests that pituitary hormones other than, or in addition to, FSH may play a major role in the restoration of spermatogenesis.…”
Section: Discussionmentioning
confidence: 61%
“…FSH will potentiate the action of LH during these steps (1,5,8,10), although FSH alone was observed to have no effect on the maturation of the spermatids in some (8,10,11), but not all (5), studies. It was suggested that the conversion of late spermatocytes to early spermatids is probably not hormonally sensitive (5,8), although this step was suppressed in testosterone-induced restoration experiments (9).…”
mentioning
confidence: 80%
“…FSH will potentiate the action of LH during these steps (1,5,8,10), although FSH alone was observed to have no effect on the maturation of the spermatids in some (8,10,11), but not all (5), studies. It was suggested that the conversion of late spermatocytes to early spermatids is probably not hormonally sensitive (5,8), although this step was suppressed in testosterone-induced restoration experiments (9). Other studies showed that spermatogenesis can be qualitatively maintained in adult rats by testosterone alone (12), while a combination of testosterone and FSH appeared to be necessary for initiation of spermatogenesis at puberty in both rat (6,13) and man (14).…”
mentioning
confidence: 80%
See 2 more Smart Citations